2021
DOI: 10.21203/rs.3.rs-937337/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparison of Tibial Anatomical-mechanical Axis Angles and Patellar Positions Between Tibial Plateau Levelling Osteotomy (TPLO) and Modified Cranial Closing Wedge Osteotomy (AMA-Based CCWO) for the Treatment of Cranial Cruciate Ligament Disease in Large Dogs With Tibial Plateau Slopes Greater Than 30° and Clinically Normal Labradors Retrievers

Abstract: Background: The objective of this study was to evaluate tibial anatomical-mechanical axis angles (AMA-angles) and proximodistal and craniocaudal patellar positions following tibial plateau levelling osteotomy (TPLO) and AMA-based modified cranial closing wedge osteotomy (CCWO) in large dogs with tibial plateau angle (TPA) >30°, to compare these postoperative positions with those of a control group of healthy normal dogs, and to assess which procedure yields postoperative morphology of the tibiae and stifles… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Because the AMA angle and TPA are strongly correlated with TPA >30°, it should be taken into consideration when a tibial plateau slope alteration procedure must be chosen (Guénégo et al, 2017(Guénégo et al, , 2020(Guénégo et al, , 2021. Good outcomes have been recorded with a modified CCWO, AMA-based CCWO to reduce the AMA angle (Guénégo et al, 2016(Guénégo et al, , 2018(Guénégo et al, , 2021. Although CBLO aligns the anatomical and mechanical axes of the proximal and distal segments (Hulse, 2014;Raske et al, 2013;Vasquez et al, 2018), the literature has not reported how many procedures result in a final AMA of 0° and whether it is possible to determine an alternative method to facilitate rotation planning by simply bringing the intercondylar eminence to the DAA line tip to obtain this result.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because the AMA angle and TPA are strongly correlated with TPA >30°, it should be taken into consideration when a tibial plateau slope alteration procedure must be chosen (Guénégo et al, 2017(Guénégo et al, , 2020(Guénégo et al, , 2021. Good outcomes have been recorded with a modified CCWO, AMA-based CCWO to reduce the AMA angle (Guénégo et al, 2016(Guénégo et al, , 2018(Guénégo et al, , 2021. Although CBLO aligns the anatomical and mechanical axes of the proximal and distal segments (Hulse, 2014;Raske et al, 2013;Vasquez et al, 2018), the literature has not reported how many procedures result in a final AMA of 0° and whether it is possible to determine an alternative method to facilitate rotation planning by simply bringing the intercondylar eminence to the DAA line tip to obtain this result.…”
Section: Resultsmentioning
confidence: 99%
“…Because the magnitude of the AMA angle has been associated with an increased risk of the development of CrCL rupture in several studies (Guénégo et al, 2017(Guénégo et al, , 2020Ševčík et al, 2022), this suggests that it should be taken into consideration when the tibial plateau slope alteration procedure must be chosen (Guénégo et al, 2020(Guénégo et al, , 2021Guénégo & Bureau, 2022). A modified cranial closing wedge osteotomy based on AMA angle (AMA-based -CCWO) was developed using the same concept of the CBLO, allowing for an alignment of the anatomic/mechanical axis following rotation of the tibial plateau slope, which could contribute to maintaining more normal stress distribution and kinematics of the stifle during weight bearing, and good outcomes have been described (Guénégo et al, 2016(Guénégo et al, , 2018(Guénégo et al, , 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the TPLO group, the mechanical axis of the CTWO group moved cranially against the anatomical axis, thus becoming the tibial recurvatum (16,37). Osseous genu recurvatum, one of the osseous deformities of the knee joint, is hyperextension of the knee.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,10 Although it is still not entirely known how the AMA-angle magnitude and consequent craniocaudal position of the patella may affect the initiation or progression of CrCL rupture, 11 these specific tibial measurements should be considered when choosing the tibial plateau slope alteration procedure. 6,11,12,30,31 Despite this, there is insufficient information indicating that the reduction of the AMAangle by itself is an aid to joint stability. 19,32 However, good to excellent results have been reported using surgical techniques that manage to reduce the AMA-angle.…”
Section: Discussionmentioning
confidence: 99%
“…19,32 However, good to excellent results have been reported using surgical techniques that manage to reduce the AMA-angle. 30,[32][33][34] The center of rotation of angulation-based leveling osteotomy (CBLO) technique aligns the proximal and distal segment anatomical/mechanical axis, maintaining approximately 30% of the normal cranial tibial thrust. 16,35 However, an evaluation of the degree of reduction in the magnitude of the initial AMA-angle with the DAA design described for planning the technique has not been reported.…”
Section: Discussionmentioning
confidence: 99%